The Moral Gatekeeper: Soccer and Technology, the Case of Video Assistant Referee (VAR) - Tamir, Ilan; Bar-eli, Michael (Frontiers in Psychology, 2021)
VAR was officially introduced into soccer regulations in 2018, after many years in which referee errors were justified as being “part of the game.” The technology’s penetration into the soccer field was accompanied by concerns and much criticism that, to a large degree, continues to be voiced with frequency. This paper argues that, despite fierce objections and extensive criticism, VAR represents an important revision in modern professional soccer, and moreover, it completes a moral revolution in the evolution of the sport as a whole. Theoretically speaking, this technology enables an improvement in the sport’s professional standards and its public image and prestige, and especially its moral standards – Fair play. Furthermore, the introduction of this technology makes it possible to discover additional weaknesses (Standardization for extra time, a clear definition of a handball offence and more) that professional soccer regulations will probably be forced to address in the future.